Unveiling sequence-agnostic mixed-chemical modification patterns for splice-switching oligonucleotides using the NATURA platform - Tommaso Tabaglio; Taniya Agarwal; Wei Yuan Cher; Jin Rong Ow; Ah Keng Chew; Priscila Yun Qian Sun; Raja Sekhar Reddy Gurrampati; Hongfang Lu; Praveena Naidu; Hong Kai Ng; Xavier Le Guezennec; Shi Yan Ng; et al. (Molecular Therapy: Nucleic Acids)
Chemical optimization of ribose has significantly advanced nucleic acid therapeutics (NATs) by improving the stability, specificity, and safety of therapies like small interfering RNAs, CRISPR-Cas9 guide RNAs, and GAPmers. Recent research has extended this approach to splice-switching oligonucleotides (SSOs), which target splicing events. Our study identifies a set of mixed-modification patterns—combining 2′-O-Methyl, 2′-MethOxyEthyl, 2′-Locked Nucleic Acid, and 2′-Constrained Ethyl ribose moieties (2′OMe, 2′MOE, LNA, and cET)—that enhance SSO potency. We term this strategy lateral mixed positional configuration, which improves SSO efficacy across various sequences and could reduce the trial-and-error process in SSO development. This advancement is supported by NAT Unlabeled Reporter Assay (NATURA), a novel platform for high-throughput quantification of NATs' functional delivery and potency. NATURA uses a reporter gene system and a comprehensive sequence library to test modifications and delivery methods, validated in a transgenic mouse model. This approach aims to accelerate NAT development and address challenges in delivering these therapies to patients.